1999
DOI: 10.1093/jn/129.7.1347
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein or Arginine Deficiency Impairs Constitutive and Inducible Nitric Oxide Synthesis by Young Rats

Abstract: Effects of dietary protein or arginine deficiency on constitutive and lipopolysaccharide (LPS)-induced nitric oxide (NO) synthesis were determined in young rats by quantifying urinary nitrate excretion. In Experiment 1, 30-d-old rats (n = 16) were divided randomly into two groups (n = 8/group) and pair-fed on the basis of body weight semipurified isocaloric diets containing 20 or 5% casein. In Experiment 2, 30-d-old rats (n = 24) were divided randomly into three groups (n = 8) and pair-fed on the basis of body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 50 publications
4
69
1
4
Order By: Relevance
“…In rats, Wu et al (34) observed a reduction in NO synthesis by constitutive NO synthase and inducible NO synthase during arginine deficiency, although the magnitude of the response was smaller in the rats than in the present study. To the authors' knowledge, no comparable studies of the influence of dietary arginine on NO synthesis exist in healthy neonates.…”
contrasting
confidence: 79%
“…In rats, Wu et al (34) observed a reduction in NO synthesis by constitutive NO synthase and inducible NO synthase during arginine deficiency, although the magnitude of the response was smaller in the rats than in the present study. To the authors' knowledge, no comparable studies of the influence of dietary arginine on NO synthesis exist in healthy neonates.…”
contrasting
confidence: 79%
“…The total nitrate and nitrite concentrations in the urine and plasma were measured by reacting with the Greiss reagent according to the procedure described by Wu et al 22) The NO metabolites excreted in the urine are expressed as total nitrate and nitrite per creatinine in the urine. Creatinine excreted in the urine was determined by using a commercial diagnostic kit (creatininetest) from Wako Pure Chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies suggest that supplemental L-arginine may be helpful in preventing harmful oxidation and reversing endothelial dysfunction [6]. In addition, supplementation with Larginine may reverse the endothelial dysfunction associated with hypercholesterolemia, smoking, and hypertension [7][8][9][10][11][12][13][14]. Some of L-arginine's antioxidant and anti-inflammatory effects are independent of NO production [15,16].…”
Section: Introductionmentioning
confidence: 99%